PENINGKATAN BRAND AWARENESS MELALUI REDESAIN KEMASAN: PENDAMPINGAN UMKM PANDAWA FOOD & COOKIES BUNULREJO - Elok Nur Hamdana; Meyti Eka Apriyani; M. Unggul Pamenang; Agung Nugroho Pramudhita; Deddy Kusbianto Purwoko Aji; Dimas Wahyu Wibowo (Jurnal Pengabdian kepada Masyarakat, 2026)
UMKM Pandawa Food & Cookies in Bunulrejo faces persistent challenges related to weak visual identity and unattractive packaging, particularly for its signature product, “Boolen.” These issues reduce product appeal and limit brand awareness in an increasingly competitive market. This community service program was designed to strengthen brand recognition through a user-centered packaging redesign using the Design Thinking approach. The stages included identifying partner problems, developing several visual concept alternatives, conducting iterative discussions and revisions with the business owner, creating functional prototypes, and testing the final design through real market trials. The redesigned packaging successfully improved the product’s visual appeal, enhanced the clarity and consistency of branding elements, and met appropriate food labeling standards. After implementation, the partner conducted user trials by distributing products using the new packaging. Feedback indicated increased consumer interest, better product visibility on digital platforms, and improved sales performance compared to the previous period. These findings demonstrate that a well-executed packaging redesign can significantly strengthen brand awareness, improve consumer perception, and support the competitiveness of MSME products in the local market.